HIV testing among Portuguese men who have sex with men - results from the European MSM Internet Survey (EMIS) - Carvalho, C (2013)
Objectives: To describe HIV testing behaviour and context of MSM in Portugal participating in the European MSM Internet Survey (EMIS). Methods: Data for the Portuguese sample were extracted and those for 5187 participants were analysed. Multivariate logistic regression models were fitted to quantify the association between participants' characteristics and HIV testing behaviour and context. Results: Seventy‐two percent of the participants had ever been tested for HIV and among those ever tested, 11% were diagnosed with HIV. Primary care was the most common testing setting for HIV‐negative men (37%). Compared to those never tested, men who had ever taken an HIV test had higher educational level (aOR 1.89, 95% CI 1.67‐2.14) and identified themselves as gay/homosexual more frequently (aOR 1.94 , 95% CI 1.70‐2.20). HIV testing odds significantly increased with the number of sexual partners in the previous 12 months. Those who reported unprotected anal intercourse (UAI) with a partner of unknown or serodiscordant HIV status in the previous 12 months were less likely to report an HIV test (aOR 0.38, 95% CI 0.33–0.44). Among those never tested or who tested negative, 41% and 22% reported UAI with a partner of unknown or serodiscordant status in the previous 12 months, respectively. Among men with diagnosed HIV, 72% were currently on antiretroviral therapy and 58% reported an undetectable viral load. More than one third (38%) of those who had detectable or unknown/undisclosed viral load reported at least one episode of UAI with a partner of unknown or serodiscordant HIV status in the last 12 months. Conclusions: Actual interventions should focus on: improving testing uptake and counselling; increasing treatment coverage; achieving and maintaining an undetectable viral load; and intensifying prevention efforts focused on consistent condom use.